Histopathological Distribution of the Gastrointestinal Tract Lesions - Singh, Mrinalini; Kafle, Santosh Upadhyaya; Kafle, Neeta; Sinha, Amrita; Rajbhandari, Prasun (Birat Journal of Health Sciences, 2021)
Introduction: Gastrointestinal (GI) diseases are common and can affect any portion of the gastrointestinal tract from the mouth to the anus.  Diseases can just shows clinical conditions like stomach pain, constipation, diarrhea which can be self- limiting. But sometimes disease may be life-threatening like malignancy. Biopsy is necessary for confirmatory diagnosis and further treatment of the patient. So histopathologic examination is  a must for all surgical procedures for confirmation and categorization of GI disorders.Objectives: This study was done to find out the various patterns of lesions of the gastrointestinal tract with its commonest age group and sex involvementMethodology: This was a prospective study of all the surgically resected GI tissue received in the Department of Pathology Histopathology unit in Birat Medical College and Teaching Hospital (BMCTH) from 1st February 2021 to 30 thApril 2021.The hematoxylin and eosin stain slides of the GI tissue received were studied and the lesions were diagnosed on their histomorphology.  According to organ, age and sex, the lesions were categorized. The data were entered in Microsoft excel and the percentage value was calculated.Results: Out of the total 344 cases 146(42.44%) were male and 198(57.56%) were female patients. The most common age range for GI lesions was 41 to 60 years comprising of 126(36.62%) of total cases. Maximum numbers of cases 160 (46.50%) were of cholecystectomies followed by appendectomies 95(27.60%). Inflammatory and benign lesions comprised 332(96.51%), 9(2.61%) were malignant tumor and 3(0.88%) were premalignant lesions. The most common inflammatory lesions and malignant tumors were chronic cholecystitis and gastric adenocarcinoma respectivelyConclusions: The study identifies that gastrointestinal lesions comprise of the most common biopsies received in the histopathology department. Early diagnosis of premalignant and malignant lesions can improve the overall survival rate of patients.